WORKLOAD, SERVICE QUALITY, AND EMPLOYEE PERFORMANCE IN A ZAKAT INSTITUTION - Fachrurrazi; Subrotul Imtikhanah (STABILITY : Journal of Management and Business, 2026)
Amil zakat institutions face persistent challenges in balancing workload distribution, employee performance, and service quality while sustaining organizational management effectiveness, particularly at small service offices that operate with limited human resources. This study explores organizational management effectiveness at the LAZISMU Bligo Service Office by examining how workload, service quality, and employee performance are experienced and connected by the people who live them daily. The study uses a descriptive qualitative case study design. Twenty five informants were purposively selected across four groups, each corresponding to the vantage point best suited to speak to a given theme: four staff members and one manager on workload, performance, and internal organizational effectiveness; ten muzakki on service quality as the institution's service exchange partners; and ten mustahik on organizational effectiveness as independent external beneficiaries. Data were collected through in-depth semi-structured interviews, field observation, and document review, then analyzed thematically through an iterative process of familiarization, coding, and theme development that combined categories drawn from organizational effectiveness and service quality literature with categories that emerged inductively from the data. Findings show that staff experience workload as proportional and manageable, sustained by a spiritual framing of work as amanah that buffers pressure and motivates contribution beyond formal duty. Muzakki describe service quality as a durable pillar of trust grounded in staff courtesy and transparent fund reporting, tempered by a recurring wish for more proactive communication. Mustahik describe organizational effectiveness less through targets than through dignity, feeling attended to rather than merely processed. Islamic values of amanah, ikhlas, and ibadah recur across all four groups as the thread binding workload, service quality, performance, and effectiveness together, carrying both theoretical and practical implications for how effectiveness is understood in Islamic philanthropic organizations.